Bring back my gerbil! - Tarbescu, Edith; e (New York : Scholastic, 1999)
Best friends Caitlin and Tyler are surprised when she tries an experiment with his gerbil and apparently turns him into a dog.
"Cartwheel books."
G2
Keywords: Gerbils -- Fiction; Dogs -- Fiction